GLOBAL TRENDS AND RESEARCH HOTSPOTS OF AEROBIC GRANULAR SLUDGE FOR WASTEWATER TREATMENT USING SCOPUS DATABASE: A BIBLIOMETRIC ANALYSIS (Malaysian Journal of Civil Engineering, 2023)
The aerobic granular sludge (AGS) system is a promising technology that is suitable for the treatment of various types of wastewaters. This system has received great attention from many researchers due to its wide range of applications and potential as a cost effective system. However, only a few reports are available in analyzing the progress of AGS research in wastewater treatment over the last 20 years. Therefore, in the present work, a bibliometric analysis was carried out to trace the global research trends and current hotspots of AGS in wastewater treatment from 1997 to 2020, based on the Scopus database. The bibliometric data was visualized using the VOSviewer software. A total of 1,347 articles were published in 160 journals across 19 subject categories, involving 50 countries and 129 academic institutions. Results showed that Bioresource Technology (175, 12%), Water Research (94, 6.96%), and Huanjin Kexue Environmental Science (78, 5.77%) dominated in the top 3 journals. Environmental Science (1036, 38%), China (716, 53%), and Harbin Institute of Technology (98, 7.28%) were the most productive subject category, country, and academic institution, respectively. The AGS research hot topics and future research directions were discovered through the analysis of the most frequently used keywords obtained in bibliometric maps.